2014
DOI: 10.1039/c4ob00827h
|View full text |Cite
|
Sign up to set email alerts
|

Multivalent glycosylated nanoparticles for studying carbohydrate–protein interactions

Abstract: Carbohydrates are essential mediators of many important extracellular binding events. Multivalent effects are often required for these binding interactions that are generally weak. Biologically significant carbohydrate-modified nanomaterials are an appealing model system for a systematic investigation of multivalent binding effects. This review seeks to highlight recent striking examples of multivalent glycosylated nanomaterials concentrating on carbohydrate-protein interactions. The specific aim is to provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 89 publications
3
36
0
Order By: Relevance
“…A variety of glyconanomaterials have been developed, such as carbohydrate-coated gold nanoparticles, carbon nanomaterials, quantum dots, silica nanoparticles, etc., and have found utilities in for example biosensing, imaging and therapeutics. [2][3][4][5][6][7][8][9][10] The binding affinity of the glyconanomaterials with their receptors is the most important feature that dictates the performance of the glyconanomaterials in these applications. In order to calculate the affinity constant, the carbohydrate density on the nanomaterials must be determined.…”
mentioning
confidence: 99%
“…A variety of glyconanomaterials have been developed, such as carbohydrate-coated gold nanoparticles, carbon nanomaterials, quantum dots, silica nanoparticles, etc., and have found utilities in for example biosensing, imaging and therapeutics. [2][3][4][5][6][7][8][9][10] The binding affinity of the glyconanomaterials with their receptors is the most important feature that dictates the performance of the glyconanomaterials in these applications. In order to calculate the affinity constant, the carbohydrate density on the nanomaterials must be determined.…”
mentioning
confidence: 99%
“…[18][19][20] Glyconanoparticles can be specifically tailored to allow for the bioanalytical detection of various biological targets. [21][22][23] Detection of such targets can be achieved by varying several properties of the carbohydratefunctionalised nanoparticles viz. : 1) the material used to create the nanocore and the methodology applied to assemble the carbohydrate on the nanoparticle surface; 2) the carbohydrate ligand itself; 3) the length of the anchor chain tethering the carbohydrate to the nanoparticle surface; and 4) the density of carbohydrate molecules on the nanoparticle surface.…”
Section: Introductionmentioning
confidence: 99%
“…To analyze the carbohydrate-protein interactions quantitatively, various glyconanoparticle systems bearing different carbohydrate epitopes have been described for the investigation of specific binding interactions through several methods. [18] These methods include surface plasmon resonance (SPR), [19] quartz crystal microbalance (QCM) techniques, [20] isothermal titration calorimetry (ITC), [21] magnetic resonance imaging (MRI), [22] fluorescence measurements, [23] and dynamic light scattering (DLS). [24] We previously reported that glyco-AuNPs can be used for labeling specific proteins on the cell surface through carbohydrate-receptor interactions.…”
Section: Introductionmentioning
confidence: 99%